Polymorphism and division of labour in a socially complex ant: neuromodulation of aggression in the Australian weaver ant, Oecophylla smaragdina - Kamhi, J. Frances (Proc Biol Sci, 2015)
Complex social structure in eusocial insects can involve worker morphological and behavioural differentiation. Neuroanatomical variation may underscore worker division of labour, but the regulatory mechanisms of size-based task specialization in polymorphic species are unknown. The Australian weaver ant, Oecophylla smaragdina, exhibits worker polyphenism: larger major workers aggressively defend arboreal territories, whereas smaller minors nurse brood. Here, we demonstrate that octopamine (OA) modulates worker size-related aggression in O. smaragdina. We found that the brains of majors had significantly higher titres of OA than those of minors and that OA was positively and specifically correlated with the frequency of aggressive responses to non-nestmates, a key component of territorial defence. Pharmacological manipulations that effectively switched OA action in major and minor worker brains reversed levels of aggression characteristic of each worker size class. Results suggest that altering OA action is sufficient to produce differences in aggression characteristic of size-related social roles. Neuromodulators therefore may generate variation in responsiveness to task-related stimuli associated with worker size differentiation and collateral behavioural specializations, a significant component of division of labour in complex social systems.